Studi Kajian Strategi Promosi Penjualan Olahan Kelapa Menjadi Keripik - Permata, Suarika Diah; Wanti Siregar, Lidia; Wigrha, Biwi Cahya; Andini, Della Surya; Rangkuty, Dewi Mahrani (CiDEA Journal, 2025)
The business product discussed by the author is coconut chips. Coconut chips are products made from white, crispy and sweet coconut flesh and have a distinctive coconut smell. In general, this product is made from coconuts aged 7-8 months, consumed as snacks or dried foods. The purpose of making coconut chips is to be an alternative for the community as a snack product that has high nutritional value. In addition, it can increase the utilization of young coconuts and can be an alternative business opportunity so as to create new jobs. The stages used in the implementation of the coconut chip business program include preparation, market research and product formulation, as well as marketing strategies.